Mobility Enhancement of P3HT‐Based OTFTs upon Blending with Au Nanorods. (16th October 2015) - Zhou, Li; Han, Su‐Ting; Zhuang, Jiaqing; Yan, Yan; Zhou, Ye; Sun, Qi‐Jun; Xu, Zong‐Xiang; Roy, V. A. L.
Abstract : The mobility enhancement of organic thin‐film transistors based on poly(3‐hexylthiophene) (P3HT) by incorporating gold nanorods (Au NRs) is reported. Through varying the doping concentration and surface modifier of the Au NRs in P3HT matrix, the P3HT/Au composite with 0.5 mg mL −1 pyridine‐capped Au NRs exhibits a hole mobility of 0.059 cm 2 V −1 s −1, this value is seven times higher than that of pristine P3HT. This remarkable improvement of mobility originates from the enhanced crystallinity and optimized orientation of P3HT after doping with Au NRs. In addition, the appropriate surface modification can produce more‐efficient hole conduction of Au NRs. Abstract : The incorporation of gold nanorods with alkylamino and pyridine ligands into a poly(3‐hexylthiophene) (P3HT) matrix leads to the mobility enhancement of P3HT‐based organic thin‐film transistors. This enhancement is attributed to the improved crystallinity of the P3HT film, and the optimized orientation of P3HT relative to the substrate.